Superimposed Whole-Body Electrostimulation Augments Strength Adaptations and Type II Myofiber Growth in Soccer Players During a Competitive Season - Filipovic, Andre; DeMarees, Markus; Grau, Marijke; Hollinger, Anna; Seeger, Benedikt; Schiffer, Thorsten; Bloch, Wilhelm; Gehlert, Sebastian (Frontiers in Physiology, 2019)
Background: The improvement of strength and athletic performance during a competitive season in elite soccer players is a demanding task for the coach. Aims: As whole-body electrostimulation (WB-EMS) training provides a time efficient stimulation potentially capable in exerting skeletal muscle adaptations we aimed to test this approach over 7 weeks in trained male soccer players during a competitive season. Hypothesis: We hypothesized that a superimposed WB-EMS will increase maximal strength and type I and type II myofiber hypertrophy. Methods: Twenty-eight male field soccer players were assigned in either a WB-EMS group (EG, n=10), a training group (TG, n=10) or a control group (CG, n=8). The regular soccer training consists of 2-4 sessions and one match per week. In concurrent, the EG performed 3 x 10 squat jumps superimposed with WB-EMS twice per week, TG performed 3 x 10 squat jumps without EMS twice per week, and the control group only performed the regular soccer training. Muscle biopsies were collected and strength tests were performed under resting conditions before (Baseline) and after the intervention period (Posttest). Muscle biopsies were analyzed via western blotting and immunohistochemistry for skeletal muscle adaptive responses. To determine the effect of the training interventions a 2x3 (time*group) mixed ANOVA with repeated measures was conducted. Results: Maximal strength in leg press (p = .009) and leg curl (p = .026) were significantly increased in EG along with a small but significant increase in type II myofiber diameter (p = .023). All of these adaptations were not observed in TG and CG. Conclusion: WB-EMS can serve as a time efficient training method to augment strength capacities and type II fiber myofiber growth in soccer players when combined with specific resistance training. This combination may therefore be a promising training modification compared to traditional strength training for performance enhancement.